4m(-3)m+2=12

Simple and best practice solution for 4m(-3)m+2=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m(-3)m+2=12 equation:


Simplifying
4m(-3) * m + 2 = 12

Reorder the terms for easier multiplication:
4 * -3m * m + 2 = 12

Multiply 4 * -3
-12m * m + 2 = 12

Multiply m * m
-12m2 + 2 = 12

Reorder the terms:
2 + -12m2 = 12

Solving
2 + -12m2 = 12

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -12m2 = 12 + -2

Combine like terms: 2 + -2 = 0
0 + -12m2 = 12 + -2
-12m2 = 12 + -2

Combine like terms: 12 + -2 = 10
-12m2 = 10

Divide each side by '-12'.
m2 = -0.8333333333

Simplifying
m2 = -0.8333333333

Reorder the terms:
0.8333333333 + m2 = -0.8333333333 + 0.8333333333

Combine like terms: -0.8333333333 + 0.8333333333 = 0.0000000000
0.8333333333 + m2 = 0.0000000000

The solution to this equation could not be determined.

See similar equations:

| 500=d | | 7x-31+5x+13=180 | | 0=-16x^2+32x+2 | | 8+4p=5p+7p | | -2.2-3y-7.4-y=-3y+3.8 | | 5x-25.2=x | | 2y/3-5/9=5/9 | | (a^2)-7a+12=0 | | -219=d | | 8x+5x+63=180 | | 7(n+11)=81 | | X+21.83=65.5 | | 5/9÷4/9 | | 8z+3-5z=3+2z-1 | | 12(n+-8)=36 | | (a^2)+7a+12=0 | | 4=0.1x-0.2x-2 | | 6x+212.85=2x+297.99 | | 0.5x-2=0.15x+5 | | 7(8+4+x)= | | Y=4x-b | | 91-166=-8(-4y)-17(2y)+y | | X=65.5 | | 5y^2-7=42 | | 3/4b=46.50 | | 45+20+0.55x=45+0.65x | | 5x+(4)(-5)=-20 | | 46.50b-3/4 | | n-20.64=-6.64 | | X+5x+y+3y+5-2= | | 600=m-12+m | | 7(-3x-1/7) |

Equations solver categories